Carbamoly-phosphate synthetase 1 (CPS1) deficiency: A tertiary center retrospective cohort study and literature review - Mahmood Noori; Omar Jarrah; Aisha Al Shamsi (Molecular Genetics and Metabolism Reports)
Background: Protein metabolism and urea production maintain protein and amino acid homeostasis in normal status. Ammonia results from amino acid turnover and is produced by intestinal urease-positive bacteria. Ammonia must be detoxified, and the urea cycle converts ammonia into urea. CPS1 is an enzyme in the urea cycle that catalyzes ammonia and bicarbonate condensation. CPS1 deficiency presents in the neonatal period with hyperammonemia, resulting in death or neurological sequelae if patients survive. Objectives/aims: To share the experience of patients with CPS1 deficiency from Tawam Hospital and to shed light on the spectrum of variants found in those patients. Methods: A retrospective chart review was done. All patients with CPS1 deficiency admitted to Tawam Hospital from 2010 to 2023 were included. Collected data included age and ammonia level at presentation, the time needed to drop ammonia level below 100 μmol/L, acute management modality provided, long-term neurological sequelae, sequence variants, severity, and duration of hyperammonemia encephalopathy, age at last follow-up, and, if applicable, survival for at least six months. Results: Only five patients with CPS1 deficiency over 13 years were found; two males and three females. Three patients are doing relatively well at 18 months, 7, and 9 years of age. The presented age was in the neonatal period except in one patient. One patient was found to have frameshift, resulting in a premature stop codon in the CPS1 gene, had a devastating course that ended with death. One patient had recurrent hyperammonemia episodes in her first year of life, which led to microcephaly and global developmental delay. One patient underwent hemodialysis, and one patient underwent peritoneal dialysis. All patients except one were on Carglumic acid which could contribute to their survival and disease control. All variants reported here are novel except one. Conclusion: Although the presentation was different in severity, three patients are doing relatively well and approaching their developmental milestones. Thus, early recognition, prompt actions to drop high ammonia level, and good follow-up plans are emphasized. Further studies are needed to correlate the genotype-phenotype of reported variants here, which can help predict the severity of CPS1 deficiency.